"Loss of polarity of basal cells" - The term revisited in the light of genomics - Debasish Pramanick; Richa Singh; Bidyut Roy; Anjana Mazumdar; Sandip Ghose (Elsevier, 2022)
The concept of polarity in development, homeostasis and pathological alteration of tissues has emerged as an interesting aspect of the concerned biology. The epithelial cells exhibit apicobasal polarity which is maintained by Crumbs complex located at apical region of tight junction, 'PAR' complex at sub-apical region of tight junction and Scribble complex at adherens junction. Any functional perturbation of these proteins cause alteration of normal epithelial physiology en-route to epithelial pathology. In this maiden scientific exercise, we have tried to explore the association of expression of cell polarity proteins in OPMD and OSCC. Here, we have chosen DLG1 as a representative of polarity protein. RNA was isolated from the tissue samples. Then cDNA was prepared by RTPCR technique. qPCR was performed on cDNA samples. Expression data was analysed on the basis of Ct values. Paired t-test was performed with normalized Ct values of disease and normal tissue to determine whether there was any significant difference in expression between them. The statistical tests were done using SPSS software. Results of this study reflected increase in DLG1 expression in high grade dysplasia. There was no significant alteration in expression of DLG1 in WDSCC where there is formation of cluster of neoplastic cells ultimately producing epithelial islands and keratin pearls. But, in case of MDSCC, when the same neoplastic cells keep on invading with minimal keratin pearl formation, they again gain the mesenchymal character in full potential. And this phenomenon supports the upregulation of DLG1 in MDSCC in our study.